Use of over-the-scope clips in the colon in clinical practice: results from a German administrative database - Horenkamp-Sonntag, Dirk; Liebentraut, Judith; Engel, Susanne; Skupnik, Christoph; Albers, David; Schumacher, Brigitte; Koop, Herbert (Endoscopy, 2020)
Background The efficacy and safety of over-the-scope (OTS) clips in the colon is limited. This study aimed to evaluate OTS clip use in the colon in routine colonoscopy.Methods Using administrative data from a large health insurance company, patients with OTS clip placement during colonoscopy were identified and analyzed by specific administrative codes. Indication for OTS clipping was analyzed, and follow-up was evaluated for surgical and repeat endoscopic interventions.Results In 505 patients, indications for OTS clips were iatrogenic perforations (n = 80; Group A), polypectomy (n = 315; Group B), colonic bleeding (n = 51; Group C), and various underlying diseases (n = 59; Group D). In 11 Group A patients (13.8 %), surgical interventions occurred, mostly within 24 hours after clipping (n = 9), predominantly overstitching (n = 8). OTS clipping during polypectomy (Group B) was for complications (e. g. bleeding in 27 %) or was applied prophylactically. Only five patients required early surgery, three of whom had colorectal cancer. In four Group C patients (7.8 %), surgical resections were performed (persistent bleeding n = 1, colorectal cancer n = 2), while six patients underwent early repeat colonoscopy for recurrent bleeding. During further follow-up (days 11–30), 17 patients underwent resection for colonic neoplasms (n = 12) or persistent bleeding (n = 4), but only one case could be directly traced back to local OTS clip complication.Conclusion Colonic OTS clipping appears safe and effective in selected indications and complications in clinical routine but must be anatomically and technically feasible, avoiding overuse.